Epistemology of Nature inspired Artificial System - Das, Amit; Singh, R.K (International Journal of Computer Sciences and Engineering, 2019)
The artificial intelligence is one of the most emerging area of research in the field of advance computing, which emphases a new direction of thought known as nature based computing or bio-inspired artificial system. The concept is based on the different organisms such as insect colonies, flock of birds or school of fish. This manuscript is presenting different algorithms which are useful to develop artificial systems by deploying different nature based ideas.